2014
DOI: 10.1007/s12010-014-1447-4
|View full text |Cite
|
Sign up to set email alerts
|

Polygalacturonase Production by Calcium Alginate Immobilized Enterobacter aerogenes NBO2 Cells

Abstract: Bacterial cells of Enterobacter aerogenes NBO2 were entrapped in calcium alginate beads in order to enhance polygalacturonase production compared to free cells. The optimized condition of 5 % (w/v) sodium alginate concentration, agitation speed of 250 rpm, and 15 beads of calcium alginate with inoculum size of 4 % (v/v; 5.4 × 10(7) cells/ml) produced 23.48 U/mL of polygalacturonase compared to free cells of 18.54 U/ml. There was about 26.6 % increment in polygalaturonase production. However, in this study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 8 publications
2
4
1
Order By: Relevance
“…Only Bacillus spp isolated where indicated to be a producer of pectinase. This agrees with different documentations of Bayoumi et al, Geetha [75][76][77][78][79][80][81][82]. Bacillus subtilis being a producer of pectinase agrees with the report of Mariam and Aruna that B. subtilis strain arium 1115 produced the highest quantity of extracellular pectinase out of the arrays of Bacillus spp assayed for [83] [80][81][82][83][84][85][86][87][88][89].…”
Section: Discussionsupporting
confidence: 90%
“…Only Bacillus spp isolated where indicated to be a producer of pectinase. This agrees with different documentations of Bayoumi et al, Geetha [75][76][77][78][79][80][81][82]. Bacillus subtilis being a producer of pectinase agrees with the report of Mariam and Aruna that B. subtilis strain arium 1115 produced the highest quantity of extracellular pectinase out of the arrays of Bacillus spp assayed for [83] [80][81][82][83][84][85][86][87][88][89].…”
Section: Discussionsupporting
confidence: 90%
“…IFVB and Citrobacter sp. IFVB were greater than reported (18Á54 and 1Á047 U ml À1 respectively) (Darah et al 2015;Tripathi and Kapoor 2018).…”
Section: Discussioncontrasting
confidence: 63%
“…Pseudomonas aeruginosa (ZS-45), isolated from orange produced maximum enzyme activity, 4.4 U/µL. Polygalacturonase production by Enterobacter aerogenes NBO 2 (18.54 U/mL) ( 17 ) was much less compared to Bacillus and Pseudomonas (4.4 U/µL each). Zeni et al ( 18 ) reported the same results for PG production by various species of Bacillus from agro-industrial waste.…”
Section: Discussionmentioning
confidence: 99%